Durvalumab plus tremelimumab in advanced or metastatic soft tissue and bone sarcomas: a single-centre phase 2 trial. Issue 9 (September 2022) - Somaiah, Neeta; Conley, Anthony P; Parra, Edwin Roger; Lin, Heather; Amini, Behrang; Solis Soto, Luisa; Salazar, Ruth; Barreto, Carmelia; Chen, Honglei; Gite, Swati; Haymaker, Cara; Nassif, Elise F; et al.
Summary: Background: Few standard treatment options are available for patients with metastatic sarcomas. We did this trial to evaluate the efficacy, safety, and changes in the tumour microenvironment for durvalumab, an anti-PD-L1 drug, and tremelimumab, an anti-CTLA-4 drug, across multiple sarcoma subtypes. Methods: In this single-centre phase 2 trial, done at The University of Texas MD Anderson Cancer Center (Houston, TX USA), patients aged 18 years or older with advanced or metastatic sarcoma with an Eastern Cooperative Oncology Group performance status of 0 or 1 who had received at least one previous line of systemic therapy were enrolled in disease subtype-specific groups (liposarcoma, leiomyosarcoma, angiosarcoma, undifferentiated pleomorphic sarcoma, synovial sarcoma, osteosarcoma, alveolar soft-part sarcoma, chordoma, and other sarcomas). Patients received 1500 mg intravenous durvalumab and 75 mg intravenous tremelimumab for four cycles, followed by durvalumab alone every 4 weeks for up to 12 months. The primary endpoint was progression-free survival at 12 weeks in the intention-to-treat population (all patients who received at least one dose of treatment). Safety was also analysed in the intention-to-treat population. This trial is registered with ClinicalTrials.gov, NCT02815995, and is completed. Findings: Between Aug 17, 2016, and April 9, 2018, 62 patients were enrolled, of whom 57 (92%) received treatment and were included in the intention-to-treat population. With a median follow-up of 37·2 months (IQR 1·8–10·1), progression-free survival at 12 weeks was 49% (95% CI 36–61). 21 grade 3–4 treatment-related adverse events were reported, the most common of which were increased lipase (four [7%] of 57 patients), colitis (three [5%] patients), and pneumonitis (three [5%] patients). Nine (16%) patients had a treatment related serious adverse event. One patient had grade 5 pneumonitis and colitis. Interpretation: The combination of durvalumab and tremelimumab is an active treatment regimen for advanced or metastatic sarcoma and merits evaluation in specific subsets in future trials. Funding: AstraZeneca.